INDONESIA DI TENGAH KESEPAKATAN ACFTA - Sinaga, Lidya Christin (Jurnal Penelitian Politik, 2010)
The ASEAN China Free Trade Area ACFTA formally took effect as ofJanuari 1 2010 The initial phase of the trade agreement was in force in early 2004 also known as the Early Harvest Programme EHP A free trade area covering trade in goods between China and the original six ASEAN members including Indonesia is to be completed by 2010 and the remainingfour by 2015 However the socialization ofEHP scheme by Indonesian government relativelypoor and made it difficultfor business sector especially Small and Medium Enterprises SMEs in Indonesia to exploit this scheme The full implementation ofACFTA on January 2010 has given strong pushes from business sectors to delay the implementation The basic problem is in our domestic capacity and capability which is not yet competitive enough to compete especially with China products Therefore this paper will analyze the impact of ACFTA on Indonesia and what should be done to counter the impacts